What are banks and bank regulation for? A consideration of the foundations for reform - Sheila C. Dow (Intervention. European Journal of Economics and Economic Policies, 2012)
The paper considers the different ways in which we can approach reform of banking regulation by reflecting on different views on the nature and purpose of money and banks. We consider first the mainstream theory of banking and the interpretation of moral hazard as an expression of calculative rational behaviour, such that reform of banking regulation is formulated in terms of financial incentives and constraints. Post-Keynesian banking theory rather emphasises banks? role in providing society's money and thus the centrality of social conventions, particularly confidence in the money asset. The key is to design regulation so as to allow banks to play their supportive role in the economy, while suppressing scope for a negative role. This approach involves a broader understanding both of moral hazard and of regulation itself.
Keywords: B50; E42; G28; 330; banking functionality; philosophical foundations of banking regulation; moral hazard